Transforming education through generative AI: a pathway to equitable learning and literacy under SDG4 - Mustapha, Nur Arfah; Ismail, Zurina; Mohd Ishar, Nor Irvoni; Omar, Zoel-Fazlee; Mior Harun, Mior Harris (UiTM Press, 2025)
The advent of Generative Artificial Intelligence (AI) represents a significant advancement in the field of education, particularly in addressing global educational disparities. This paper presents a knowledge transfer programme that integrates generative AI into teaching and learning practices, aligned with Sustainable Development Goal 4 (SDG 4), specifically SDG 4.5 and SDG 4.6. The programme focuses on reducing inequalities in education and improving literacy and numeracy rates among youth and adults, particularly within vulnerable and marginalized communities. The implementation of AI technologies in educational settings demonstrates their potential in fostering inclusive, equitable, and high-quality education, promoting lifelong learning opportunities for all.